ChemInform Abstract: Solvent‐Free Aminocarbonylation of Iodobenzene in the Presence of SILP‐Palladium Catalysts. Issue 39 (September 2016) - Papp, M.; Szabo, P.; Sranko, D.; Skoda‐Foeldes, R.
Abstract: Heterogeneous palladium catalysts prepared by immobilization of palladium on supported ionic liquid phases are effectively used as reusable catalyst for the synthesis of carboxylic amides.